Lineage Tracing Reveals the Dynamic Contribution of Pericytes to the Blood Vessel Remodeling in Pulmonary Hypertension. Issue 3 (March 2020) - Bordenave, Jennifer; Tu, Ly; Berrebeh, Nihel; Thuillet, Raphaël; Cumont, Amélie; Le Vely, Benjamin; Fadel, Elie; Nadaud, Sophie; Savale, Laurent; Humbert, Marc; Huertas, Alice; Guignabert, Christophe
Abstract : Objective: Excessive accumulation of resident cells within the pulmonary vascular wall represents the hallmark feature of the remodeling occurring in pulmonary arterial hypertension (PAH). Furthermore, we have previously demonstrated that pulmonary arterioles are excessively covered by pericytes in PAH, but this process is not fully understood. The aim of our study was to investigate the dynamic contribution of pericytes in PAH vascular remodeling. Approach and Results: In this study, we performed in situ, in vivo, and in vitro experiments. We isolated primary cultures of human pericytes from controls and PAH lung specimens then performed functional studies (cell migration, proliferation, and differentiation). In addition, to follow up pericyte number and fate, a genetic fate-mapping approach was used with an NG2CreER;mT/mG transgenic mice in a model of pulmonary arteriole muscularization occurring during chronic hypoxia. We identified phenotypic and functional abnormalities of PAH pericytes in vitro, as they overexpress CXCR (C-X-C motif chemokine receptor)-7 and TGF (transforming growth factor)-βRII and, thereby, display a higher capacity to migrate, proliferate, and differentiate into smooth muscle-like cells than controls. In an in vivo model of chronic hypoxia, we found an early increase in pericyte number in a CXCL (C-X-C motif chemokine ligand)-12-dependent manner whereas later, from day 7, activation of the canonical TGF-β signaling pathway induces pericytes to differentiate into smooth muscle-like cells. Conclusions: Our findings reveal a pivotal role of pulmonary pericytes in PAH and identify CXCR-7 and TGF-βRII as 2 intrinsic abnormalities in these resident progenitor vascular cells that foster the onset and maintenance of PAH structural changes in blood lung vessels. Abstract : Supplemental Digital Content is available in the text.